A MEANS OF CREATING AN ARTISTIC MODEL OF PERSONALITY IN DREISER’S WORKS - Fayziyeva Komila Axrorovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation. In his work, Dreiser directly assesses the character’s personality and actions. For example, describing Hurstwood’s sad state after his separation from Carrie, Dreiser writes: “The hotel manager felt a certain interest in the man. He did not know where to put him, but at the same time, Hurstwood’s voice was so sincere that he involuntarily wanted to help him.” However, sometimes the writer refrains from such direct descriptions of the objects and personalities of his characters.